2016
DOI: 10.7566/jpsj.85.034711
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic Cluster Glass Phase Embedded in a Paramagnetic and Metallic Host in Non-Uniform Magnetic System CaRu1−xScxO3

Abstract: We have investigated both static and dynamic magnetic properties of polycrystalline CaRu 1−x Sc x O 3 system in order to clarify the role of Sc ions as a disorder for magnetic ordering. We have observed typical features of a ferromagnetic cluster glass state below around 40 K: (i) a broad, frequency-dependent peak in the ac magnetic susceptibility, (ii) a slow relaxation of the magnetization, and (iii) a continuous increase in the dc magnetic susceptibility in field cooling process. The composition dependence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…These behaviors in M (T ) are the characteristics of the formation of the FM cluster-glass state; it is expected that the FM clusters develop and start interacting (or freezing) below ∼ T ir , and the majority of the FM clusters then freeze below ∼ T * , yielding the very small and large hysteresis below T ir and T * , respectively, in M (T ) between the FC and ZFC conditions. These features are also observed in the other cluster-glass systems [35,36].…”
Section: A Magnetic Propertiessupporting
confidence: 67%
“…These behaviors in M (T ) are the characteristics of the formation of the FM cluster-glass state; it is expected that the FM clusters develop and start interacting (or freezing) below ∼ T ir , and the majority of the FM clusters then freeze below ∼ T * , yielding the very small and large hysteresis below T ir and T * , respectively, in M (T ) between the FC and ZFC conditions. These features are also observed in the other cluster-glass systems [35,36].…”
Section: A Magnetic Propertiessupporting
confidence: 67%
“…In addition, MR(H, 2 K) shows a hysteretic curve with a sign change in low magnetic fields. These features correspond to the magnetization M. 11) As shown in the inset of Fig. 2, the magnetic hysteresis curve strongly correlates with the MR(H, 2 K) curve.…”
Section: Resultsmentioning
confidence: 66%
“…No jump at Tc is seen in zero magnetic field, indicating a magnetic glassiness. [20][21][22] Our dynamic magnetic measurements 11) have suggested that the Sc-induced ferromagnetism results from a cluster glass state with a long relaxation time. A similar featureless specific heat has been reported in CaRu1-xTixO3.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The glassy state of CRO clusters could be confirmed by the measurement of AC magnetic susceptibility. [ 35 ]…”
Section: Discussionmentioning
confidence: 99%